The Airflow Reversal Law in Ventilation System after Coal and Gas Outburst in Tunneling Roadway - Junhong Si; Yiqiao Wang; Genyin Cheng; Lin Li; Yitian Shao; Tan Li; Wei Hu (Shock and Vibration)
Considering the coal and gas outburst phenomenon in the mining space, this paper analyzes the main characteristics of coal and gas outburst accidents, defines the outburst airflow reversal degree, and constructs a simplified topology graph of tunneling ventilation system, while the air door is not destroyed. Using the numerical simulation method, this paper elaborates on the relationship between the outburst pressure and airflow reversal degree. The results indicate that the inlet pressure increases to 264 hPa and the outlet pressure increases to 289 hPa when the outburst pressure increases from 1 hPa to 1 MPa, and the relative variation coefficient of pressure decreases from 1501.5 to 1.62 in the inlet of return airway and decreases from 2002 to 1.65 in the outlet of return airway. Furthermore, the air velocity decreases from −1.38 to −284.44 m/s in the inlet and increases from 3.10 to 297.38 m/s in the outlet. Moreover, the gas concentration of the inlet and outlet in return airway increases rapidly with the increase of outburst pressure. When the outburst pressure is greater than 0.15 MPa, the gas concentration will be over 98% in tunneling ventilation system. This paper also finds out a cubic polynomial relationship existing between the reversal degree and the outburst pressure. It provides the prediction of coal and gas outburst and serves as a guidance in case mine ventilation disturbances occur.